1979
DOI: 10.1083/jcb.82.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Replication of mammalian DNA in vitro. Evidence for initiation from fiber autoradiography.

Abstract: We have used fiber autoradiography to examine the DNA product made in vitro in a lysed cell system . CHO cells were treated with 0 .01% Brij-58 and the lysates were incubated at 30°C in a complete reaction mixture for in vitro DNA synthesis with [ 3H)thymidine triphosphate ([3H]TTP) as the radioactive tracer. Fiber autoradiograms prepared from the DNA showed that it was synthesized on tandemly arranged replication units that were of average size of 20 Jim, very similar to the size of units found in vivo . The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Furthermore, at the normal rate of polymerization (50 to 100 bases per s) (32), Okazaki units are finished within a few seconds. This period might be prolonged to around 30 s or 1 min if the polymerization rate in vitro is 10 times slower than that in vivo (14,22,35). As the time course of the cell-free synthesis shows a linear increase during the first 15 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, at the normal rate of polymerization (50 to 100 bases per s) (32), Okazaki units are finished within a few seconds. This period might be prolonged to around 30 s or 1 min if the polymerization rate in vitro is 10 times slower than that in vivo (14,22,35). As the time course of the cell-free synthesis shows a linear increase during the first 15 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro replication system used is well characterized and active for a number of rodent cell lines (2,3,(10)(11)(12). It continues semiconservative DNA synthesis at an initial rate of up to 50% of that in intact cells (10) and probably supports some initiation as well (2, 4).…”
mentioning
confidence: 99%
“…We have found that the ts BN-2 phenotype is expressed in vitro (submitted for publication). The in vitro replication system used is well characterized and active for a number of rodent cell lines (2,3,(10)(11)(12). It continues semiconservative DNA synthesis at an initial rate of up to 50% of that in intact cells (10) and probably supports some initiation as well (2,4).…”
mentioning
confidence: 99%